Drug Management Cycle Before and After the COVID-19 Pandemic at the Samarinda Ulu District Pharmacy - Yunita, Shella; Marthilia Alim, Muthia Dewi (Universitas Muhammadiyah Kalimantan Timur, 2023)
The purpose of this study is to determine the cycle of drug management before and after as well as the differences in the drug management cycle of the Covid-19 pandemic in pharmacies. A type of quantitative research with a descriptive method that describes problems that occur in the present and ongoing times in certain popylations. Analyze the data using the cross sectional or cross-sectional design method. Use the Wilcoxon Signed Rank Test to find out whether or not there is a difference. The results stated that there were 2 differences in negative values after the pandemic. Positive ranks or differences (positive) there are 15 respondents who experienced an increase in value having positive data and Ties are the same value obtained, here there are 7 respondents whose post-pandemic value is the same as the value before the pandemic or there is no increase in the value before the pandemic or there is no increase in. This research is a scientific work, the results of this research will be useful to increase knowledge and can be used as a reference or data source for other related research to the drug management cycle before and after the COVID-19 pandemic in pharmacies.